Thermography as a method for evaluating human vegetative reactions - Liuzina, Kseniya M.; Rutkevich, Svetlana A.; Mikulich, Raman Yu.; Kabanau, Dzmitry M.; Lebiadok, Yahor V. (Experimental Biology and Biotechnology, 2019)
The possibility of using the thermal imaging method to assess the level of blood flow in the course of building thermograms of the surface of the hands of healthy volunteers before and after the load on the muscles was studied in this paper. The results obtained using the thermal imaging method provide objective information about the degree of blood supply to the tissues, which opens up new perspectives for evaluating skin blood flow in the dynamics. The technique is absolutely safe, non-invasive, versatile and easy to perform.
Keywords: thermal imaging method; temperature of skin surface; blood flow; muscle contraction